Mayor Matit Centina the manogpatigayon of Pontevedra, Negros Occidental, 1982-1991. - Parpa, Errol C (2003.)
The study seeks to understand the role and character of the political middleman in the political culture of Pontevedra, Negros Occidental as reflected in the life of Mayor Damaso "Matit" Centena. The objectives were: to describe the concept of political middleman held by the people of Pontevedra, to qualify Matit Centena as political middleman of the town, and to discuss the milieu, the character and the role of Matit as political middleman. To answer the objectives, 16 key respondents from various sectors of the place were interviewed as to their understanding of the nature of politics in Pontevedra and their concepts about the political actors therein. The study found out that the respondents have the concepts of the elite, the masses, and the political middleman. They consider the sugar planters belonging to the La Carlota Miling District as the elite which they call dalagko. These dalagko are rich, have many properties, have interests, spend and choose their candidates for Pontevedra. The masses which call pigado, where those ordinary voters like those working in the hacienda, fishermen, vendors, jobless, whose existence is typified by day-to-day survival. Lastly, the political middleman which they call manugpatigayon is situated in the middle trying to reconcile the interests of the two sectors. Matit Centena is a manugpatigayon because he has the trust of both sectors to deliver their respective interests. Matit was able to respond to the emergency needs of the pigado. If not, he provides alternative solutions and these pleased them. Matit, on the other hand, was trusted by the dalagko primarily because he can deliver the votes needed by them to get more concessions from the national government. Until his death, Matit was able to maintain his good reations with the two camps. He being good looking, fun to be with, gentle, generous, patient, friendly and good speaker helped in enhancing his personality which made him more attractive to the two sectors. For a manugpatigayon to emerge in a community, there must be a clear demarcation between the elite and the masses. This paper is a contribution to the efforts of the writers of political science that are trying to enrich the patron-client framework of analysis by introducing new actors. In this study, the manugpatigayon.
Research Project (Undergraduate, Bachelor of Arts in Political Science-History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Centina, Matit -- Mayor -- Pontevedra, Negros Occidental